Networked control system for the guidance of a four-wheel steering agricultural robotic platform - Godoy, Eduardo Paciência [UNESP]; Tangerino, Giovana Tangerino; Tabile, Rubens André; Inamasu, Ricardo Yassushi; Porto, Arthur José Vieira (Hindawi, 2012)
A current trend in the agricultural area is the development of mobile robots and autonomous vehicles for precision agriculture (PA). One of the major challenges in the design of these robots is the development of the electronic architecture for the control of the devices. In a joint project among research institutions and a private company in Brazil a multifunctional robotic platform for information acquisition in PA is being designed. This platform has as main characteristics four-wheel propulsion and independent steering, adjustable width, span of 1,80m in height, diesel engine, hydraulic system, and a CAN-based networked control system (NCS). This paper presents a NCS solution for the platform guidance by the four-wheel hydraulic steering distributed control. The control strategy, centered on the robot manipulators control theory, is based on the difference between the desired and actual position and considering the angular speed of the wheels. The results demonstrate that the NCS was simple and efficient, providing suitable steering performance for the platform guidance. Even though the simplicity of the NCS solution developed, it also overcame some verified control challenges in the robot guidance system design such as the hydraulic system delay, nonlinearities in the steering actuators, and inertia in the steering system due the friction of different terrains. Copyright © 2012 Eduardo Pacincia Godoy et al.
Keywords: Agricultural areas; Angular speed; Autonomous Vehicles; Control challenges; Control strategies; Current trends; Different terrains; Distributed control; Electronic architecture; Hydraulic system; Information acquisitions; Joint projects; Precision Agriculture; Private companies; Research institutions; Robot guidance; Robot manipulator; Robotic platforms; Steering actuators; Steering performance; Steering systems; Agriculture; Control nonlinearities; Diesel engines; Electronic guidance systems; Hydraulic equipment; Machine design; Mergers and acquisitions; Networked control systems; Robot applications; Robotics; Wheels; Four wheel steering